Subject specific hand and forearm musculoskeletal 3D geometries using high-resolution MR images. Issue 1 (2nd January 2019) - Marin, Frédéric; Devos, Pierre; Hansen, Clint; Charleux, Fabrice; Robert, Ludovic; Mansour, Khalil Ben
Abstract: Magnetic medical imaging (MRI) is commonly used to 3D rendering of musculoskeletal structures. However, due to technical limitations of the device e.g. the coil, high-spacial resolution is available only for a small field of view. However in the case of hand and forearm investigation, and due to the long tendon and small bones, both high special and a large field of view are required. It is the aim of this study to propose the in silico enlargement of the field of view to 3D visualise all hand's bones and tendons paths. Using MRI clinical routine sequence, we detailed a procedure of hand immobilisation by alginate and registration of up to four consecutive MRI volume acquisitions. In order to validate our method, we evaluated the accuracy of the anatomical structures segmentation (i), the robustness of the registration by a sensitivity analysis (ii) and the accuracy of the 3D reconstruction by comparison with computer tomography imaging (iii). The results demonstrated a mean error of 1 mm on the 3D external surface and of 0.94 mm on the localisation of the hand bones. We also tested different hand sizes and showed that the field of view could be increased up to 2.3 time compared to the original one.